Histopathological study of cutaneous and soft tissue fungal infections - Kaliyamoorthy, Siva; Srinivasan, Sowmya (International Journal of Research in Medical Sciences, 2017)
Background: The spectrum of fungal infection is varied ranging from cutaneous to invasive infections. In most instances it is asymptomatic and localized. In immunocompromised individuals it can be invasive, involving the visceral organs and can become symptomatic. The objective was to study and document the spectrum of fungal lesions histopathologically diagnosed in the Department of Pathology, SMVMCH, India. Methods: Cases for a period of 7 years spanning from January 2007- December 2013 were taken for this study. The diagnosis was based on the hematoxylin & eosin (H&E) stained sections and special stains like periodic acid schiff (PAS) and Gomori’s methenamine-silver (GMS) were used to identify the fungal elements. Results: A total number of 10 cases were positive for fungal infection. All were found in the skin, mucous membrane and soft tissue location. Among these, 3 were Maduromycosis, 3 were phaeohyphomycosis, 2 were dermatophytosis and 1 case each of aspergillosis and chromoblastomycosis were seen. All patients had localized infection and there was no evidence of immunocompromised status. No invasive fungal lesion was found over the 7 year period of study. Conclusions: H&E stain is helpful for identification of fungal elements and tissue reaction, since most of these cases (7 of 10 cases) presented with pigmented fungi. Histopathology is mandatory for ensuring diagnosis and for further management since these patients clinically present as asymptomatic soft tissue lesions.